Improving Students’ Reading Comprehension Through Film Clips to the Eighth Grade Students of SMP Negeri 29 Samarinda - Rindana, Ratu Vina; Putra, Hedyan (JOINT: Journal of Inspirational English Language Teaching, 2024)
This study investigates the impact of using English film clips with subtitles on improving reading comprehension and language skills among eighth-grade students at SMP Negeri 29 Samarinda. Conducted during the 2023–2024 academic year, the quasi-experimental research involved 33 students from Class 8A, divided into an experimental group and a control group. Over eight weeks, the experimental group engaged with film clips featuring subtitles, while the control group followed conventional English lessons. Data collection included pre- and post-tests using a validated 25-item multiple-choice reading test, as well as surveys and observation checklists. Statistical analysis, including paired sample t-tests, revealed significant improvements in the experimental group’s reading comprehension compared to the control group. Post-test results showed a substantial rise in performance, with 20% of the experimental group achieving “excellent” scores, a category absent in their pre-test results. The findings underscore the effectiveness of multimedia learning tools in fostering student engagement and enhancing academic outcomes. This study supports integrating English film clips into language instruction to create dynamic learning environments that cater to diverse learning styles and improve educational outcomes. Future research could extend these findings by exploring the long-term effects of such multimedia interventions and their applicability across different educational contexts.